Health Shocks in China : Are the Poor and Uninsured Less Protected? - Lindelow, Magnus; Wagstaff, Adam (World Bank, Washington, DC, 2012)
Health shocks have been shown to have important economic consequences in industrial countries. Less is known about how health shocks affect income, consumption, labor market outcomes, and medical expenditures in middle- and low-income countries. The authors explore these issues in China. In addition to providing new evidence on the general impact of health shocks, they also extend previous work by assessing the extent of risk protection afforded by formal health insurance, and by examining differences in the impact of health shocks between the rich and poor. The authors find that health shocks are associated with a substantial and significant reduction in income and labor supply. There are indications that the impact on income is less important for the insured, possibly because health insurance coverage is also associated with limited sickness insurance, but the effect is not significant. They also find evidence that negative health shocks are associated with an increase in unearned income for the poor but not the non-poor. This effect is however not strong enough to offset the impact on overall income. The loss in income is a consequence of a reduction in labor supply for the head of household, and the authors do not find evidence that other household members compensate by increasing their labor supply. Finally, negative health shocks are associated with a significant increase in out-of-pocket health care expenditures. More surprisingly, there is some evidence that the increase is greater for the insured than the uninsured. The findings suggest that households are exposed to considerable health-related shocks to disposable income, both through loss of income and health expenditures, and that health insurance offers very limited protection.